Detection Of Nematode Worm Eggs In The Feces Of Domestic Chicken (Gallus domesticus) In Karang Bongkot Village Labuapi District West Lombok Regency - Waskita, Teguh Dwi; Ningtyas, Novarina Sulsia Ista’In; Agustin, Alfiana Laili Dwi (Mandalika Veterinary Journal, 2022)
Domestic chicken (Gallus domesticus) is one type of poultry that has experienced domestication and is spread throughout the archipelago. Chicken consumed by humans should be in a healthy condition and free from various types of parasites.Â Information about Domestic chicken infected with parasites is needed to maintain animal health and prevent the occurrence of zoonotic diseases.Â Research has been carried out on Domestic chicken in Karang Bongkot Village, Labuapi District, West Lombok Regency with the aim of detecting nematode worms in Domestic chicken. Samples were taken as many as 5 chicken feces and examined by the native and floating method in the Equine Clinical Skills Center (CSC) laboratory of the Faculty of Veterinary Medicine, Mandalika Universitas of Mataram, and then identified based on their morphology. Two samples were positive for nematode infection. The results of this study succeeded in detecting nematodes that infect native chickens as Heterakis gallinarum species.